Use of a Lightweight Portable Fluoroscopy Device for Obtaining Weightbearing Ankle Images. Issue 4 (November 2022) - Ashkani-Esfahani, Soheil; Schermann, Haggai; Zhao, John Z.; Lubberts, Bart; Kaiser, Philip; Waryasz, Gregory R.
Category: Ankle; Other Introduction/Purpose: Portable fluoroscopy devices provide point-of-care imaging in emergency and out-patient clinics. In patients suffering from ankle syndesmosis injuries, imaging under physiologic load can lead to more accurate diagnosis, particularly in subtle cases. In this study, we compared weightbearing images obtained using a novel lightweight portable battery-powered fluoroscopy device with a conventional radiography device regarding syndesmosis examination measurements. Methods: In this prospective study, eleven healthy participants underwent bilateral three-view weightbearing imaging of both ankles using a radiography (X-ray group) device and a portable fluoroscopy system (Smart-C group). Radiographic measurements were done by two observers on anteroposterior, mortise, and lateral views were compared between the two techniques. These measurements included talar tilt, tibiofibular clear space, tibiofibular overlap, plafond malleolar angle, medial distal tibial angle, medial clear space, lateral distal tibial angle, anterior and posterior tibiofibular distance were measured using the appropriate view. Data were compared between the two techniques; the interobserver agreement was calculated within each group. P<0.05 was considered statistically significant. Results: Comparing the two imaging modalities, there was no significant difference between the measurements in Smart-C and X- ray groups except plafond malleolar angle. The overall interobserver agreement was excellent between the two observers. There was no significant difference between the measures by the two observers and between the bilateral ankles. Conclusion: Our results support the use of weightbearing images using portable fluoroscopy device as an alternative for the conventional radiography systems, particularly in limited-resource settings.